Self-efficacy, approach, and teacher’s practice in the writing teaching (European Journal of Education and Psychology, 2009)
We present a research about the analysis of the teacher’s practice in the teaching of the writing. The sample was composed by 137 teachers from language area, working in 30 different Kindergarten’s schools and Primary Schools. We applied a device (PRAES) which include the theoretical approach that teachers have about how the students learn, the believes about the effects of those instructions, the writing correction, the teaching methods (formal and natural), and the teacher’s self-efficacy related with those teaching. Data suggest that the PRAES presents an adequate reliability and validity, besides it provides a precise description of the problem; signaling that the teachers show positive opinion in the device, and we can predict some variables from the instrument. And last, we discuss and comments results and its implications. We discuss the shortcomings; and we signal as desirable to implement researches which reduce these problems; besides, we suggest to extend this type of study in other fields, not only in writing.Key words: Self-efficacy, theoretical approach, teaching in writing, teacher’s practice.